Kantian and Utilitarian Ethics on Capital Punishment - Udoudom, Mfonobong David; Bassey, Samuel Akpan; Okpe, Okpe; Adie, Timothy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
It is an indisputable fact that most societies in the world agrees that if a person violates the laws, he/she should be penalized.Â  However, the variations appear when it involves what sensibly punishment ought to be applied, predominantly for major crimes like murder. Death penalty, which as well referred to as execution or capital punishment, is one amongst these variations which have caused several arguments and debates between its opponents and supporters. Today, numerous countries are attempting to seek out different sanctions for major crimes like life imprisonment relatively to capital punishment. This research tries to take a look at the idea of capital punishment from Kantian and Utilitarian ethics perspectives.